2015
DOI: 10.1186/s40608-015-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Pediatric Weight Management Registry (CANPWR): baseline descriptive statistics and comparison to Canadian norms

Abstract: BackgroundA pilot study was conducted to assess the feasibility of establishing a multi-site CANadian Pediatric Weight management Registry (CANPWR) containing individual, family and weight management program information.MethodsStandardized baseline data were collected to characterize CANPWR participants (n = 310) in comparison to a sample of age-matched Canadian children measured in the nationally representative Canadian Health Measures Survey (CHMS; n = 3,788). This study compared demographic, anthropometric,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Adolescents with obesity exhibit suboptimal lifestyle behaviours related to nutrition, physical activity, sedentary behaviour and sleep , likely owing to factors that either negatively (barriers) or positively (enablers) influence their choices. To our knowledge, no review has yet synthesized the evidence in relation to lifestyle behaviours of adolescents with obesity seeking weight management.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with obesity exhibit suboptimal lifestyle behaviours related to nutrition, physical activity, sedentary behaviour and sleep , likely owing to factors that either negatively (barriers) or positively (enablers) influence their choices. To our knowledge, no review has yet synthesized the evidence in relation to lifestyle behaviours of adolescents with obesity seeking weight management.…”
Section: Introductionmentioning
confidence: 99%
“…8 The Canadian Pediatric Weight Management Registry published baseline data in 2015. 10 Since no such registry exists in the United States for youth with obesity seeking treatment, the Pediatric Obesity Weight Evaluation Registry (POWER) was developed to address current gaps about effective intervention strategies for the treatment of pediatric obesity in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Are sites able to retain participants to enable longitudinal research data collection and analysis, regardless of whether individuals discontinue clinical care for weight management?). Data collected during our pilot were compared and contrasted with normative Canadian data, which highlighted the increased health risks present in children referred for weight management [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…CANPWR is a prospective, national, multi-centre, observational cohort study created to evaluate the individual-, family-, and program-level determinants of (i) health outcomes (cardiometabolic health and health related quality of life) at baseline, (ii) change in health outcomes over a 3-year period, and (iii) attrition from multidisciplinary pediatric weight management clinics located across Canada. Results from our pilot study, which included five clinical sites, were reported previously [ 4 ]. The main study [ 3 ] is ongoing and was designed to enroll 1600 2–17 year-olds with overweight or obesity from 10 clinics over three years.…”
Section: Introductionmentioning
confidence: 93%